2015
DOI: 10.1097/mpg.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Adequacy and Associated Factors in a Nationwide Sample of German Toddlers

Abstract: Nutritional quality measured by total nutrient intake is altogether high in German toddlers, although NQI decreased with increasing age. The NQI is independent of social class. The positive association with formula intake can be explained by the general enrichment of vitamins and minerals of these products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
5
16
1
5
Order By: Relevance
“…For Germany median intake values of vitamin D are available for healthy toddlers. In the German Representative Study of Toddler Alimentation (GRETA) median values ranged between 2.3 µg/day for 13–18 months old and 1.1 µg/day for 25–36 months old toddlers [ 32 ]. For the VELS study similar median values were reported for 1–3 year old (1.2 µg/day for males; 1.1 µg/day for females) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Germany median intake values of vitamin D are available for healthy toddlers. In the German Representative Study of Toddler Alimentation (GRETA) median values ranged between 2.3 µg/day for 13–18 months old and 1.1 µg/day for 25–36 months old toddlers [ 32 ]. For the VELS study similar median values were reported for 1–3 year old (1.2 µg/day for males; 1.1 µg/day for females) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the VELS study similar median values were reported for 1–3 year old (1.2 µg/day for males; 1.1 µg/day for females) [ 19 ]. It is not possible to evaluate the level of inadequacy for median values using the EAR cut-point method but the authors of the respective studies stated that vitamin D intake was low compared to recommendations [ 19 , 32 ]. In Germany supplementation of vitamin D is recommended for infants from the first week of life for the next 12 to 18 months depending on season of birth [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Deutschland wurde eine mangelhafte Versorgung mit Folsäure, Vitamin D, Eisen und Jod, und zwar deutlich unter den Zufuhrempfehlungen bei 525 Kleinkindern zwischen dem 10. und 36. Lebensmonat beobachtet [26]. Eisen, Jod, Zink sind für die körperliche und kognitive Entwicklung essenziell.…”
Section: Daten Zur Vegetarischen Ernährung Bei Kindernunclassified
“…Versorgung von Kindern (13-36 Monate) mit Mikronährstoffen entsprechend der Empfehlung für die Altersgruppe[26]. Folgen einer unzureichenden Zufuhr von Mikronährstoffen in Schwangerschaft und Stillzeit für die kindliche Entwicklung.…”
unclassified
“…Bemerkenswert ist, dass für die kognitive Entwicklung vor allem Jod, Eisen und Vitamin D besonders wichtig sind. In einer der wenigen Untersuchungen bei Kleinkindern (10-36 Monate) in Deutschland waren dies genau die Mikronährstoffe, die deutlich unter den Empfehlungen lagen [10].…”
Section: Auswirkungen Des Mangelsunclassified